2013
DOI: 10.1038/nm.3424
|View full text |Cite
|
Sign up to set email alerts
|

Host-cell sensors for Plasmodium activate innate immunity against liver-stage infection

Abstract: Before they infect red blood cells and cause malaria, Plasmodium parasites undergo an obligate and clinically silent expansion phase in the liver that is supposedly undetected by the host. Here, we demonstrate the engagement of a type I interferon (IFN) response during Plasmodium replication in the liver. We identified Plasmodium RNA as a novel pathogen-associated molecular pattern (PAMP) capable of activating a type I IFN response via the cytosolic pattern recognition receptor Mda5. This response, initiated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
306
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(326 citation statements)
references
References 51 publications
15
306
1
4
Order By: Relevance
“…The liver develops a robust IFN response to liver-stage Plasmodium in a mouse model of infection. In this system, using either hepatocyte IFN-␣␤R-deficient or myeloid IFN-␣␤R-deficient mice, it was shown that a primary antiparasitic IFN response was driven almost exclusively by the hepatocytes, whereas the myeloid-derived IFN responses played a role later in infection (51). Our study therefore mirrors these findings in showing that IFN responses in the liver are the primary drivers of antimicrobial responses, while infiltrating immune cells play a supporting role.…”
Section: Discussionsupporting
confidence: 74%
“…The liver develops a robust IFN response to liver-stage Plasmodium in a mouse model of infection. In this system, using either hepatocyte IFN-␣␤R-deficient or myeloid IFN-␣␤R-deficient mice, it was shown that a primary antiparasitic IFN response was driven almost exclusively by the hepatocytes, whereas the myeloid-derived IFN responses played a role later in infection (51). Our study therefore mirrors these findings in showing that IFN responses in the liver are the primary drivers of antimicrobial responses, while infiltrating immune cells play a supporting role.…”
Section: Discussionsupporting
confidence: 74%
“…In addition to TLR7/TLR9-dependent mechanisms (160,161), type I IFNs can be induced in a STING, TBK1, IRF3/IRF7-dependent manner via AT-rich stem-loop DNA (162). P. berghei-derived RNA also can trigger IFN-b production in a melanoma differentiation-associated protein 5/MAVS-dependent manner (163). However, it is unknown how these pathogen products gain access to the cytosol.…”
Section: Plasmodiummentioning
confidence: 99%
“…Type I IFNs were shown to mediate protection against blood-stage (164) and liver-stage (163,165) malaria in infected animals. However, recent studies revealed that type I IFNs increase host susceptibility to cerebral malaria (162,166).…”
Section: Plasmodiummentioning
confidence: 99%
“…This second-generation GAP3KO showed a much better safety profile in more stringent preclinical tests [26], and has recently completed successful Phase I safety trials in humans in which it appears safe and immunogenic [ In addition to the development of novel vaccine strategies, the access to liver stages afforded by rodent models allows for the interrogation of innate immune responses. Once thought to be immunologically inert, the liver stages of the parasite have recently been found to indeed induce innate immune responses that are capable of limiting parasite growth [27][28][29]. How exactly the parasite is sensed is still under investigation [30], and it is also unknown how these early innate events could influence the ensuing adaptive response.…”
Section: Lessons Learned From Rodent Malaria Modelsmentioning
confidence: 99%
“…Once thought to be immunologically inert, the liver stages of the parasite have recently been found to indeed induce innate immune responses that are capable of limiting parasite growth [27][28][29]. How exactly the parasite is sensed is still under investigation [30], and it is also unknown how these early innate events could influence the ensuing adaptive response.…”
mentioning
confidence: 99%